Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, dan Reputasi Auditor terhadap Audit Delay pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2020 Menggunakan Regresi Logistik - Hardianti Hafid; Ansari Saleh Ahmar; Zulkifli Rais (Program Studi Statistika Fakultas MIPA UNM, 2023)
This research aims to determine whether profitability, company size, and auditor reputation significantly influence audit delay using binary logistic regression analysis. The research results indicate that profitability has a significant individual (partial) effect on audit delay, while company size and auditor reputation do not have a significant individual (partial) effect on audit delay